The Signaling Role of Corporate Social Responsibility - Tomer Blumkin; Yoram Margalioth; Adi Sharoni (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine the role of CSR as a mechanism for private provision of public goods. We argue that corporations are using CSR to signal high product quality and demonstrate that signaling gives rise to an excessive level of contributions that offsets the positive externality, which causes the under-provision of public goods. We analyze the tax policy implications of such assertion. Accounting for this offset would call for a decrease in (and potentially elimination of) the subsidy offered to corporations engaged in CSR activities.
Keywords: H20; H40; K30; 330; signaling; corporate social responsibility; public goods; Pigouvian taxation